Problem-Based Learning Model with Experimental Task Method Triggers Critical Thinking Skills - Icananda Fransiska; Slamet Hariyadi; Mochammad Iqbal (Universitas Tidar, 2019)
The ability to think critically is the main ability needed for graduates in the 21st century. In this regard the purpose of this study is to determine the effect of the Problem-Based Learning learning model with experimental task methods that can trigger critical thinking skills. This type of research is a quasi-experiment using pre-test and post-test. The population used is the XII grade students of SMA Negeri 4 Jember in the 2018/2019 academic year. The research sample used was selected through purposive random sampling. The analysis used is Covariance Analysis. The results showed that the average difference in the value of critical thinking skills of the experimental class students was higher than the control class, which was 31 for the experimental class and 24 for the control class, with significance results (Sig = 0,000). This is because PBL is a learning model that uses contextual problems so that students actively build knowledge and can accommodate the development of critical thinking skills. In conclusion, the Problem-Based Learning learning model with the experimental assignment method triggers an increase in students' critical thinking skills.